The test of "Sims-Huhner" modifying endocervical sampling - Ascenzo Cabello, Jorge (2015)
250 infertile couples, in our particular inquiry, revised for the past six years, we have made personally, 120 Sims-Huhner tests on 90 women. We have divided the "Take Endocervical" in "endocervical sampling: outer third" and "Take Endocervical: internal 2/3" whose technique and interpretation of results obtained detail, we also suppress the classic rest half an hour post-coital reasons we discussed. Whenever Huhner practice test, routinely studied simultaneously in the "Crystallization Cervical Mucus" and Spinngarkeit, which are essential for us to assess the Sims-Huhner to not completely normal sperm. The 3/4 tests were conducted between the twelfth and fifteenth day of the cycle, 80% of cases performed with a sexual abstention of three to seven days, and in 90% of marriages samples between three and five hours was obtained after SSR We observed good and regular reception macroscopic vaginal sperm in 42% of cases and 66.6% microscopically. In over half the cases there is a different degree of hostility in the outer 1/3 and 2 / 3 internal endocervix. The hostility of endocervical sperm medium is 2.3 times higher among inmates 2/3 1/3 in its external endocervical canal.